Anisakis simplex products impair intestinal epithelial barrier function and occludin and zonula occludens-1 localisation in differentiated Caco-2 cells. - Noelia Carballeda-Sangiao; Isabel Sánchez-Alonso; Alfonso Navas; Susana C Arcos; Pilar Fernández de Palencia; Mercedes Careche; Miguel González-Muñoz (Public Library of Science (PLoS), 2020)
BACKGROUND:Anisakis spp. are nematode parasites found in a wide range of marine organisms. Human beings may accidentally become infected, showing the symptoms of anisakiasis and allergic responses. There has been evidence of increased intestinal permeability in A. simplex-sensitized subjects and that specific IgE titres increase in some allergic patients when fishery products are re-introduced into their diet. The aims of this work were to study the effect of A. simplex crude extract on the intestinal integrity and permeability by using Caco-2 cell monolayer. To analyse the capacity of Ani s 4 allergen to cross the epithelial barrier. METHODOLOGY/PRINCIPAL FINDINGS:Cellular bioenergetics, transepithelial electrical resistance, viability, permeability, reactive oxygen species generation and immunofluorescent staining of tight junction proteins were analysed. A. simplex crude extract compromises the Caco-2 cell monolayer integrity in a dose-dependent manner. This effect is detected at 1 hour of culture and integrity is recovered after 24 hours of culture. The epithelial barrier disruption is accompanied by an increase in paracellular permeability and reactive oxygen species production and by a delocalization of occludin and zonula occludens-1. Finally, Ani s 4, a thermostable and resistant to digestion allergen with cystatin activity, is able to cross the epithelial barrier in Caco-2 monolayer and reach a cumulative mean percentage of 22.7% of total concentration in the basolateral side after 24 hours of culture. CONCLUSIONS/SIGNIFICANCE:Our results demonstrate that A. simplex induces an early and reversible alteration of integrity and permeability of Caco-2 cell monolayer and that an underlying mechanism of this effect would involve the oxidative stress and disruption of epithelial tight junctions. Additionally, it has been shown that Ani s 4 allergen is able to cross the epithelial barrier. These findings could explain the increased intestinal permeability observed in Anisakis-sensitized patients, the changes over time in IgE sensitization to A. simplex allergens, and the specific IgE persistence in Anisakis allergy.